The Influence of Mother's Characteristics, Facilities, and Reinforcing Factors on Giving Complete Basic Immunization to Infants - Indri Hardiyanti; Asfriyati Asfriyati; Sri Rahayu Sanusi (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
The coverage of complete basic immunization in Indonesia still has not reached the Strategic Plan target of 92.9%. IDL coverage at Sadabuan Health Center of 86,5% is still low and far from the immunization target set at 95%. The purpose of this study was to determine the effect of maternal characteristics (occupation and parity), enablers (knowledge and trust), and reinforcers (husband support and health worker support) on the provision of complete basic immunization in infants at the Sadabuan Health Center. The research method used was analytic observational with a quantitative research approach using a case control study research design. This research was conducted at the Sadabuan Health Center. This research was conducted from June 2022 to January 2023. The sample in this study was 148 people, consisting of 74 case samples and 74 control samples. The sampling technique used purposive sampling. Data analysis Univariate analysis with descriptive, bivariate analysis with chi-square test and multivariate analysis with multiple logistic regression test. The results of this study, There is a relationship between knowledge and the provision of complete basic immunization in infants at the Sadabuan Health Center (p-value=0,042; OR=6,411; 95% CI=0,756-54,890). There is a relationship between husband support and the provision of complete basic immunization in infants at the Sadabuan Health Center (p-value=0.001; OR=15,377; 95% CI=5,567-42,473). There is a relationship between the help of health workers with the provision of complete basic immunization in infants at the Sadabuan Health Center (p-value=0.003; OR=11,406; 95% CI=1,421-91,561). There is an influence of knowledge, husband support, and health worker support on the provision of complete basic immunization, which is 0.693 x 100% = 69.3%. Suggestions to health workers to provide counseling about complete basic immunization to mothers who have children under five to increase maternal knowledge about the importance of immunization in children. Keywords: Complete Basic Immunization, Public Health Center